Design and testing of the key technology of the cotton direct seeding machine - Song, WEI; Hongyun, Liu (Frontiers in Plant Science, 2025)
The paper aims to slove the problems of low sowing depth qualification index and poor seeding stability during in summer direct-sown cotton in the Yangtze River Basin China. To this end, a cotton seeder with rotary tillage and electric drive seeding was designed. In order to satisfy the agronomic requirements of summer direct-sown cotton, the key structural parameters of this planter were determined, and the key factors affecting the stability of seeding depth were derived. The test method of rotary orthogonal was adopted, with the initial traction angle, initial spring increment, and Working speed of the machine serving as the test factors, and the sowing depth qualification index and sowing depth consistency coefficient of variation serving as the test indexes. The results demonstrated when the initial traction angle was set to 0°. the initial spring increment was 15mm, and the Working speed was 3km·h−1, the sowing depth qualification index was obtained to be 95.59%, and the sowing depth consistency coefficient of variation was 7.38%. A test was conducted to assess the accuracy of the speed control of the electric drive seed dispenser of the sowing system. The plant spacing was set at 15, 18, and 20 cm, and the speed was set at 4.01-6.10 km·h−1. The results demonstrated the overall mean adjustment time for the speed of the seed dispenser disk was 1.04 seconds, with a standard deviation of 0.36; the overall mean steady-state error was 0.28 r/min, with a standard deviation of 0.21 r/min; the overall mean control accuracy was 98.86%, with a standard deviation of 1.01. A field test was conducted with a set plant spacing of 15 cm and a seeder speed that was not fixed. The sowing plant spacing was able to focus on the set plant spacing within the range of the qualified grain spacing (15 ± 3 cm) of the emergence of seedlings. The average sowing emergence Conformity index was 86.48%, with a minimum of 83.81%.